The grid management system in contemporary China: Grass-roots governance in social surveillance and service provision - Mittelstaedt, JC (SAGE Publications, 2021)
How should we understand the formation of the grid management system (网格化管理) of grass-roots governance in China? In this article, I argue that the grid system is an extension of existing governance structures. Facing conflicting central messaging, local grid development encountered isomorphic pressures, leading grids to resemble higher-level administration and to inherit a top–down and stability-focused mode of operation. To support this argument, I analyse five aspects: shifts in elite-level discourse, the proliferation of the grid system, recruitment standards for grid members, grid members’ tasks, and their assessment. Showcasing wide local variety, the grid system retains a managerial approach while collapsing service provision into security.